ASSESSMENT MODELS IN DEEP LEARNING AT SCHOOL - Lumban Gaol, Paltiman (Universitas Dharmawangsa Medan, 2025)
Deep learning in elementary schools emphasizes students’ active engagement in constructing meaningful understanding through critical thinking, problem-solving, collaboration, and reflection. To achieve these goals, an assessment model capable of evaluating both the learning process and outcomes authentically and comprehensively is required. This conceptual article aims to analyze various assessment models relevant to supporting deep learning in elementary schools, including formative assessment, authentic assessment, project-based assessment, portfolio, and performance rubrics. This study employs a qualitative approach using a literature review (conceptual study) method. Data were collected from scholarly articles, research findings, and policy documents related to the Merdeka Curriculum and 21st- century learning assessment. The data were analyzed qualitatively and descriptively through processes of reduction, categorization, and synthesis to identify patterns in the application of assessment models within the context of deep learning in elementary schools. The findings reveal that integrating multiple assessment models plays a crucial role in realizing deep learning. Formative assessment helps teachers monitor students’ learning progress and provide continuous feedback; authentic and project-based assessments encourage the application of knowledge in real-life contexts; portfolios support self- reflection and track competency development; and performance rubrics ensure objectivity and transparency in evaluation. The integration of these five assessment models strengthens students’ learning motivation, higher-order thinking skills, creativity, collaboration, and reflection. This study concludes that assessment should not merely serve as a tool for measuring learning outcomes but should function as an integral part of the learning process, acting as assessment as learning. Therefore, elementary school teachers need to design assessments aligned with the principles of the Merdeka Curriculum, as the integration of deep learning and authentic assessment is key to developing reflective, creative, and competitive learners who meet the demands of 21st-century education.